A system theory approach for designing cryptosystems based on hyperchaos - G. Grassi; S. Mascolo (IEEE Transactions on Circuits and Systems I: Fundamental Theory and Applications, 1999)
In this paper a general methodology for designing chaotic and hyperchaotic cryptosystems is developed. The basic idea is to make the decrypter a nonlinear observer for the state of the encrypter. Referring to this concept, some propositions are given which enable the plaintext to be retrieved if proper structural properties of the chaotic system hold. The proposed tool proves to be powerful and flexible, since a wide class of cryptosystems can be designed by exploiting different chaotic and hyperchaotic circuits. The advantages of the suggested approach are illustrated in detail. In particular, the utilization of hyperchaos-based cryptosystems, as well as the increased complexity of the transmitted signal, make a contribution to the development of communication systems with higher security.
Keywords: Cryptography; Chaotic communication; Communication system security; Flexible printed circuits; Equations; Signal generators; Design methodology; Communication systems; Oscillators; Chaos